Deglacial landscapes and the Late Upper Palaeolithic of Switzerland. (1st July 2020) - Reade, Hazel; Tripp, Jennifer A.; Charlton, Sophy; Grimm, Sonja B.; Leesch, Denise; Müller, Werner; Sayle, Kerry L.; Fensome, Alex; Higham, Thomas F.G.; Barnes, Ian; Stevens, Rhiannon E.
Abstract: The presence of people in Switzerland in recently deglaciated landscapes after the Last Glacial Maximum represents human utilisation of newly available environments. Understanding these landscapes and the resources available to the people who exploited them is key to understanding not only Late Upper Palaeolithic settlement in Switzerland, but more broadly human behavioural ecology in newly inhabited environmental settings. By applying bone collagen stable isotope analysis (δ 13 C, δ 15 N and δ 34 S) to faunal remains from Late Upper Palaeolithic localities in Switzerland, we investigate animal ecology and environmental conditions during periods of human occupation. High and relatively uniform δ 34 S values indicate that landscapes north of the Jura Mountains provided comparatively stable environmental conditions, while lower and more variable δ 34 S values on the Swiss Plateau suggest a dynamic landscape with diverse hydrological and pedological conditions, potentially linked to regionally different patterns of permafrost thaw. This contrasts with the archaeological record that appears relatively uniform between the two regions, suggesting people were employing similar subsistence behaviours across a range of environmental settings. The pattern of change in δ 15 N across the deglacial period appears consistent between areas that remained ice-free throughout the LGM and those that were glaciated. Most notable is a period of exclusively low δ 15 N values between 15, 200 and 14, 800 cal. BP, which could relate a regional expansion of floral biomass in response to environmental change. Highlights: Melting of the Alpine ice sheet provided new landscapes for animals and humans. Collagen δ 13 C, δ 15 N and δ 34 S indicates diverse environments during the Lateglacial. Previously ice-covered and ice-free areas display different δ 34 S and similar δ 15 N. δ 34 S differences may relate to location-specific permafrost thaw and soil processes. δ 15 N reflects regional scale environmental change.